Impact of reimbursement reform on Finnish occupational health service trends in 2018–2022: an interrupted time series analysis - Mervi Viljamaa; Riitta Sauni; Mikko Korhonen; Katri Oksanen; Tiia Reho (BMJ Open)
Objectives In Finland, the reimbursement system for occupational health services (OHSs) was reformed on 1 January 2020 to shift the focus from curative care to preventive OHS and promote employees’ work ability. We investigated the OHS trends and how the reimbursement affected them.Design A register-based study that used moving averages to visualise OHS trends in 2018–2022. To detect the impact of the reform, we used two types of interrupted time series (ITS) analyses: a linear regression model (ITS linear model) and an analysis of variance (ANOVA) lagged dependent variable model (ITS ANOVA).Setting Retrospective register data (2018–2022) of a major OHS provider in Finland.Outcome measures Time spent on OHS activities and the number of OHS activities per 1000 individuals per month. Level and slope changes in these measures in the ITS linear model, as well as the changes in these measures in the ITS ANOVA.Results After the reimbursement reform, the trend of preventive OHS shifted from a decline to a rise. Among nurses, the ITS linear model also showed changes of 0.6 hours (95% CI: 0.2 to 0.9) and 0.9 activities (95% CI: 0.2 to 1.7) per 1000 individuals per month. Throughout the study period, the trend of work ability health examinations for both physicians and nurses rose, with a monthly slope change of 0.03 hours (95% CI: 0.01 to 0.04) per 1000 individuals among nurses in the ITS linear model. We observed a descending trend in curative care with a monthly decrease of 14.3 hours (95% CI: −25.5 to −3.1) and 32.4 activities (95% CI: −64.1 to −0.1) per 1000 individuals by all professionals in the ITS ANOVA.Conclusions After the 2020 reimbursement reform, the focus of OHS shifted from curative care to preventive OHS. It is likely that the reform affected these changes, although other factors may also have influenced them.